Center-Pivot-Irrigated Dry-Edible Bean Cost-Return Budget - O'Brien, Daniel M.; Dumler, Troy J. (My University, 1999)
This publication projects a budget that reflects expected income and costs based on typical center-pivot-irrigated dry-edible bean production practices in western Kansas.
MF998_1999_10
Keywords: MF999; Economics; Crops; MF